KEPEMIMPINAN KEPALA SEKOLAH BERDASARKAN KECERDASAN EMOSIONAL (EQ) DI SDN 2 KAMPUNG BARU KOTA BANDAR LAMPUNG - Septi Kusumawati; rahayu ningsih, sri (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2026)
Emotional Intelligence (EQ) in educational leadership has become a significant focus in efforts to enhance school quality. This study aims to examine the practices of school principals’ leadership based on emotional intelligence at SDN 2 Kampung Baru, Kota Bandar Lampung. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews, observations, and documentary studies. The research aims to investigate the role of emotional intelligence (EQ) in the leadership of school principals at SDN 2 Kampung Baru, Kota Bandar Lampung. A qualitative approach is used to explore how emotional intelligence affects leadership practices in the school environment. Data were collected through in-depth interviews with school principals, teachers, administrative staff, and parents of students. The findings indicate that emotional intelligence plays a crucial role in shaping the leadership style of school principals. Principals with high levels of emotional intelligence tend to be better at understanding and managing their own emotions and those of others, thus building good relationships with staff, students, and parents. This has a positive impact on the conducive school climate for learning, teamwork, and students’ academic achievement. Additionally, principals with high EQs are also more adaptive in facing challenges and conflicts, and are better able to provide emotional support to staff members and students in overcoming difficulties. They are also capable of motivating and inspiring others to achieve common goals. The results of this study provide a deeper understanding of the importance of emotional intelligence in leadership practices in the school environment. The practical implications include the need for a more holistic approach to leadership development that not only focuses on technical competencies but also on emotional intelligence aspects in the training and development of school principals at SDN 2 Kampung Baru, Kota Bandar Lampung, and possibly elsewhere.